2022
DOI: 10.1186/s13073-022-01043-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 IgA and IgG in human milk after vaccination is dependent on vaccine type and previous SARS-CoV-2 exposure: a longitudinal study

Abstract: Background Breast milk is a vehicle to transfer protective antibodies from the lactating mother to the neonate. After SARS-CoV-2 infection, virus-specific IgA and IgG have been identified in breast milk, however, there are limited data on the impact of different COVID-19 vaccine types in lactating women. This study is aimed to evaluate the time course of induction of SARS-CoV-2-specific IgA and IgG in breast milk after vaccination. Methods In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
4
36
0
1
Order By: Relevance
“…We observed that the IgG levels increase after the second dose of the Sputnik V and ChAdOx1‐S, with 100% of the participants showing IgG positivity in milk and serum. Similar observations were previously reported for both, mRNA and adenoviral based vaccines ( 27 , 28 ). This rapid increase of IgG after the second dose is consistent with a specific B lymphocyte memory that will prime a faster response with higher antibodies levels ( 33 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that the IgG levels increase after the second dose of the Sputnik V and ChAdOx1‐S, with 100% of the participants showing IgG positivity in milk and serum. Similar observations were previously reported for both, mRNA and adenoviral based vaccines ( 27 , 28 ). This rapid increase of IgG after the second dose is consistent with a specific B lymphocyte memory that will prime a faster response with higher antibodies levels ( 33 ).…”
Section: Discussionsupporting
confidence: 91%
“…This rapid increase of IgG after the second dose is consistent with a specific B lymphocyte memory that will prime a faster response with higher antibodies levels ( 33 ). In contrast, we observed that the IgA levels remained constant between the two doses, as it was reported in previous studies with adenoviral-based vaccines (Ad26.COV2.S and ChAdOx1‐S) ( 27 , 28 , 35 ). Heterogeneous dynamics in IgG and IgA antibody levels can be associated to their diverse functions.…”
Section: Discussionsupporting
confidence: 82%
“…This is especially important for our vulnerable populations, such as the elderly, and oncological and immunosuppressed patients, and it requires further, in-depth research. On the other hand, the role of the microbiota linked to COVID-19 has not yet been studied in newborns, but it is shown that through breastfeeding, vaccinated women [ 76 , 77 , 78 , 79 , 80 , 81 , 82 ] confer immunity to their children; an increase in IgG and IgA antibodies against SARS-CoV-2 [ 83 , 84 , 85 , 86 ] and consequent decrease in the risk of hospitalization was demonstrated [ 87 , 88 ]. Preliminary studies on these positive effects had concerned the analysis of these antibodies also at the level of the umbilical cord and placenta [ 89 , 90 , 91 ].…”
Section: Microbiota and Sars-cov-2 Infectionmentioning
confidence: 99%
“…BNT162b2 (BioNTech and Pfizer) and mRNA-1273 (Moderna) are mRNA-based vaccines approved by the Food and Drug Administration (FDA) to use against COVID-19 (74, 75). In addition, two vector-based vaccines AZD1222 (Oxford/ AstraZeneca) and Ad26.COV2.S (Johnson & Johnson/Janssen) are widely used worldwide (76)(77)(78)(79)(80). However, due to the timing of vaccine approval, there is currently limited data on vectorbased vaccines in pregnancy and lactation, and for purposes of this review we will focus on mRNA vaccines.…”
Section: Immune Responses In Human Milk Following Covid-19 Vaccinationmentioning
confidence: 99%